Data representation by fuzzy conditional statements - Torres, Germano Lambert; Silva, Luiz Eduardo Borges; Rossi, Ronaldo (Revista Ciências Exatas, 2008)
An alternative mathematical tool to yield a data model is presented. This model is represented by fuzzy conditional statements, where the premise has a fuzzy meaning and the consequence is a mathematical equation. An algorithm is proposed to calculate the parameters of these statements. The inference method used is presented. These models can be used in many studies and in control processes. Illustrative examples for power system load modelling and forecasting are presented using real world data.